2010
DOI: 10.1111/j.1939-1676.2009.0457.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of the Muscularis Propria in Cats with Diffuse Small Intestinal Lymphoma or Inflammatory Bowel Disease

Abstract: Background: An ultrasonographic pattern of thickened muscularis propria in the small intestine and lymphadenopathy have been associated with gastrointestinal lymphoma and inflammatory bowel disease (IBD) in cats.Objectives: To investigate the association of these imaging biomarkers with IBD and lymphoma in cats. Animals: One hundred and forty-two cats with a histologic diagnosis of normal small intestine (SI) (n 5 56), lymphoma (n 5 62), or IBD (n 5 24).Methods: Retrospective case review. Pathology records fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(154 citation statements)
references
References 14 publications
9
139
5
1
Order By: Relevance
“…No cats in the IBD group had disease deeper than the mucosal layer. A relationship between the thickness of the muscularis layer and the extent of the neoplastic lymphocytic infiltration has been described previously, 7 with the muscularis thickening giving increased odds of transmural disease to the depth of the submucosa. This is supported by the current results in which the majority of bowel segments had transmural disease histologically.…”
Section: Discussionmentioning
confidence: 61%
“…No cats in the IBD group had disease deeper than the mucosal layer. A relationship between the thickness of the muscularis layer and the extent of the neoplastic lymphocytic infiltration has been described previously, 7 with the muscularis thickening giving increased odds of transmural disease to the depth of the submucosa. This is supported by the current results in which the majority of bowel segments had transmural disease histologically.…”
Section: Discussionmentioning
confidence: 61%
“…The reported ultrasonographic features of small cell intestinal lymphoma in cats include diffuse intestinal wall thickening (most specifically, a thickened muscularis propria) with or without preservation of wall layering and mesenteric lymph node enlargement(17,31). In the current study, these were also common findings in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in cats have suggested that thickening of specific wall layers can occur in response to GI disease. 4,6,9 In one study, diagnoses of lymphocyticplasmocytic enteritis and foreign bodies were associated with thickening of the muscularis layer in four cats. 4 In a case report of small bowel infarction in a cat caused by an aortic thromboembolism, a series of US evaluations documented progressive, focal mucosal and submucosal layer prominence, with final loss of normal wall layering over a period of 48 h. 9 In these studies, normal GI layer thicknesses measurements were not reported, and the observation of layer thickening or prominence was subjectively assessed.…”
Section: Introductionmentioning
confidence: 99%